Customer response to service encounter linguistics. Issue 5 (10th August 2018) - Zolfagharian, Mohammadali; Hasan, Fuad; Iyer, Pramod
Abstract : Purpose: Focused on multicultural service encounters, this paper aims to argue that the interplay between customer language preference, employee choice and use of language affects perceived interaction quality, which in turn influences loyalty, customer brand identification and positive word-of-mouth. Design/methodology/approach: Using Mexican Americans (Spanish) as the focal ethnic group (language), a 3 (contexts: Fast food-English; Post office-English; Post office-Spanish) × 4 (scenarios: customer language preference adhered to; adapted to; mixed; ignored) between-subject scenario-based experiment was conducted. Findings: Customers perceive a higher, or at least equal, level of interaction quality when the employee choice of language adheres to their preference than when the employee switches to their preferred language after missing it initially. Both of these scenarios lead to significantly higher interaction quality compared to when the employee ignores customer language preference or combines elements from two languages throughout the interaction. The adverse effects of ignoring customer preferred language or mixing it with another language are accentuated among customers with low ethnic identification and those with low level of bilingualism. Prior findings regard the interplay among interaction quality, and the remainder of outcomes variables were also corroborated. Research limitations/implications: The findings add to the literature that examines the dynamics of intercultural service encounters and draws attention to employee choice and use of language and its impact on a host of service outcomes, with interaction quality serving as a key mediator. Practical implications: This study highlights the need for service firms to consider customer language preferences and train and empower employees to meet customer expectations. To the extent that the increasingly viable segments of minority customers remain underserved in most developed markets, this study provides insights into cultivating a profitable customer segment. Originality/value: This study demonstrates the role of employee choice and use of language and its consequences.